Modification of nanoclay using transition metal ion and its effect on mechanical, physical, and thermal properties of wood-plastic composites - Yadav, Sumit Manohar (2017)
In this study, wood-plastic composites (WPCs) were fabricated from Polypropylene (PP), Wood flour (WF), Maleic anhydride grafted polypropylene (MAPP) and nanoclay using extrusion followed by an injection molding technique. The effect of organoclay, montmorillonite (MMT) and transition metal ion (TMI) modified nanoclay which were incorporated into WPCs was studied. The TMI modification was intended to achieve a good dispersion of the nanoclay into WPCs with fewer agglomerates. The TMImodification of the MMT nanoclay was carried out using Copper (II) Chloride. The nanoclay content in the composite was varied at four different loadings (1 to 5 weight percentages). The modification process had proved successful, as a high amount of copper ions were detected in the Energy Dispersion X-ray analysis (EDX) and even distribution of the nanoclay was obtained in Field Emission Scanning Electron Microscope (FESEM). X-Ray Diffraction (XRD) data with higher d-spacing values was obtained for TMI-modified nanoclay which suggests that a good intercalated structure has been achieved. TMI-modified nanoclay showed higher degradation temperature in Thermo Gravimetric analysis (TGA) analysis which indicates that modification of nanoclay had improved the thermal stability. Scanning Electron Microscope (SEM) micrographs had illustrated lesser holes, cracks, and agglomerates in WPCs loaded by TMI-modified nanoclay due to the modification of nanoclay which enables an even distribution of the nanoclay into the composite. The highest increase in tensile strength was obtained for 1 wt% of organoclay and TMI-modified nanoclay incorporated WPCs. Further addition of nanoclay had decreased mechanical properties due to the agglomeration of nanoclay. Same like mechanical properties, surface mechanical properties and surface creep behaviour were exhibited with higher value at 1 wt% of organoclay and TMI-modified nanoclay loading into the WPCs. The thermal stability was also improved in the organoclay and TMI-modified nanoclay reinforced WPCs. WPCs reinforced by organoclay and TMI-modified nanoclay decreased the water absorption of composite due to the formation of higher compatibility between nanofiller and the polymer matrix. The optimization study was conducted using a response surface methodology (RSM). The optimum tensile strength was obtained as 33.46 MPa at 72 wt% of polypropylene content and 1.38 wt% of nanoclay.